2006
DOI: 10.1093/rheumatology/kel108
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-related apoptosis-inducing ligand and osteoprotegerin serum levels in psoriatic arthritis

Abstract: In summary, BMD is decreased in one-third of patients with PsA, and predominantly men with PsA suffer from osteoporosis. While TRAIL serum levels are increased in PsA and correlated with CRP levels, neither TRAIL nor OPG serum levels are correlated with BMD or markers of bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 22 publications
3
65
0
2
Order By: Relevance
“…These findings could be of relevant importance in determining the correct number of working OBs which are needed to build new bone. Moreover, in pathological conditions, in which the overexpression of TRAIL has been demonstrated [36][37][38][39][40][41], our data suggest that TRAIL could contribute to the impairment of OB differentiation by targeting the apoptosis of OB precursors.…”
Section: Discussionmentioning
confidence: 65%
“…These findings could be of relevant importance in determining the correct number of working OBs which are needed to build new bone. Moreover, in pathological conditions, in which the overexpression of TRAIL has been demonstrated [36][37][38][39][40][41], our data suggest that TRAIL could contribute to the impairment of OB differentiation by targeting the apoptosis of OB precursors.…”
Section: Discussionmentioning
confidence: 65%
“…PsA itself is characterised by synovitis, enthesitis, dactylitis and spondylitis usually accompanied with skin and very often nail psoriasis [8]. Apart from chronic inflammation, medications such as methotrexate or steroids, and sometimes prolonged immobilization due to joint pain have been recognized as possible risk factors that contribute to bone loss in those patients [9].In spite of that in PsA there is a lot of controversy about it, as the results of bone status in these patients are still conflicting [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was detected between the pSS group and healthy controls (p>0.01). studies on patients with SLE (11,12) and psoriatic arthritis (26), it was found that sTRAIL levels were higher than in healthy controls but there was no correlation between disease activity and sTRAIL levels. When we assessed the relationships between disease activity and sTRAIL levels, we found no significant correlation between sTRAIL level and the tender and swollen joint count, ESR, CRP and DAS28 score.…”
Section: Resultsmentioning
confidence: 97%